Efektivitas Penerapan Teknik 3M (Mengamati, Meniru dan Menambahi) Terhadap Kemampuan Menulis Teks Drama pada Siswa Kelas VIII UPT SMP Negeri 37 Medan - Dina Ulva Jelita Rumahorbo; Azhar Umar (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study was made to determine for sure whether the 3M technique (observing, imitating and adding) is the right technique to be used in improving the ability to write drama texts in grade VIII students of UPT SMP Negeri 37 Medan. The type of data used in this study is quantitative primary data, namely data obtained from the field where the research was conducted. The data used in this study was obtained based on the results of post-test tests on both samples, namely the control class and the experimental class, where the experimental class was given learning to write drama texts with 3M techniques, while the control class was given conventional learning techniques. After testing and data analysis, conclusions can be drawn. First, the average score in the experimental class was 76.05 which was included in the good category. Secondly, the average score in the control class was 47.09 which falls into the category of very less. Third, the results of the hypothesis test, it turned out that the t_0 obtained was greater than t_tabel namely, 14.55 > 1.69, so that H_0 was rejected, and the hypothesis  accepted. Thus, it can be concluded that the 3M technique is indeed effective in improving students' ability to write drama texts.